Research on Key Parameters and Engineering Experiments of Coal Gangue Slurry Filling Technology - Hao Pan; Shengrong Xie; Wenzhe Gu; Tianqi Song; Fengqi Qiu; Dongdong Chen (Applied Sciences)
In this paper, a gangue grouting filling technology in goafs is proposed based on the dual requirements of not affecting the average production of tens of millions of tons of coal from mines and achieving the large-scale underground disposal of coal gangue, and the technology’s principle and critical technical issues are elucidated. This article explores practical problems, such as how coal gangue forms slurry, how the long-distance pipeline transportation of coal gangue slurry can be realized, and how coal gangue slurry intervenes in the gaps of collapsed rocks in goafs through laboratory experiments and large-scale experiments. Finally, the feasibility of this technology was verified through on-site underground industrial experiments to explore a technically and economically feasible avenue for the underground filling of coal gangue in tens of millions of tons of coal from mines in western China.